2017
DOI: 10.3389/fnhum.2017.00374
|View full text |Cite
|
Sign up to set email alerts
|

Task Complexity Modulates Sleep-Related Offline Learning in Sequential Motor Skills

Abstract: Recently, a number of authors have advocated the introduction of gross motor tasks into research on sleep-related motor offline learning. Such tasks are often designed to be more complex than traditional key-pressing tasks. However, until now, little effort has been undertaken to scrutinize the role of task complexity in any systematic way. Therefore, the effect of task complexity on the consolidation of gross motor sequence memory was examined by our group in a series of three experiments. Criterion tasks alw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…Another reason could be that greater cognitive efforts induce fatigue, which can be successfully restored in sleep. The importance of task complexity was emphasized in a recent study [ 81 ] wherein the sleep-related improvements were absent with shorter sequences and more regular movement patterns.…”
Section: Factors Influencing the Effect Of Sleep On Gmlmentioning
confidence: 99%
“…Another reason could be that greater cognitive efforts induce fatigue, which can be successfully restored in sleep. The importance of task complexity was emphasized in a recent study [ 81 ] wherein the sleep-related improvements were absent with shorter sequences and more regular movement patterns.…”
Section: Factors Influencing the Effect Of Sleep On Gmlmentioning
confidence: 99%
“…3 The plurality of gross motor paradigms developed so far has revealed inconsistencies in the findings, especially related to sleep-dependent consolidation. [4][5][6] For instance, Genzel et al 7 reported sleep-dependent gains in performance following sequential motor learning with the lower limbs (ie, dance choreography), while no-sleep benefits were observed following whole-body motor adaptation (ie, learning to ride an inverted-steering bicycle). 4 Nevertheless, it has been postulated that gross motor learning has to be sequentially structured, sufficiently challenging, and acquired explicitly in order to benefit from the sleep consolidation effect.…”
Section: Introductionmentioning
confidence: 99%
“…To address this issue, various fundamental and ecological gross motor paradigms have been used, from uni‐ and bimanual to whole‐body movements 3 . The plurality of gross motor paradigms developed so far has revealed inconsistencies in the findings, especially related to sleep‐dependent consolidation 4‐6 . For instance, Genzel et al 7 reported sleep‐dependent gains in performance following sequential motor learning with the lower limbs (ie, dance choreography), while no‐sleep benefits were observed following whole‐body motor adaptation (ie, learning to ride an inverted‐steering bicycle) 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Although most previous studies that assessed the effect of sleep on motor skill learning utilized simple tasks that focus on fine motor skills ( 13 ), evidence suggests that research findings on simple motor tasks cannot be generalized to gross and more complex motor skills ( 20 ). This is evident by studies that found the effect of sleep on motor skill learning differs with task complexity ( 40 ). In this current study, participants practiced a novel functional motor task that is similar to daily activities and is often practiced in a rehabilitation setting.…”
Section: Discussionmentioning
confidence: 93%